The Korean Dao: Daoist experiences on the Korean Peninsula - Costantini, Filippo (2025)
This paper analyzes the presence and influence of Daoism within the cultural and religious context of Korea, emphasizing its historical development and contemporary relevance. Daoism, as a multifaceted and adaptable tradition, has left a significant mark on Korean spirituality, particularly through its integration into New Religious Movements (NRMs). Despite its limited institutional presence in Korea compared to other traditions like Buddhism or Christianity, Daoist principles and practices have deeply permeated Korean culture. The Daesoon Jinrihoe movement, emerging in the early 20th century, is a prominent example of this influence, revitalizing Daoist concepts within a modern framework. This study highlights the continuous and transformative role of Daoism in shaping Korean spiritual identity, illustrating its enduring relevance beyond its Chinese origins.